RESTORATIVE JUSTICESEBAGAI UPAYA ALTERNATIF PENYELESAIAN TINDAK PIDANADI INDONESIA BERDASARKAN PERATURAN KEJAKSAAN REPUBLIK INDONESIANOMOR 15 TAHUN 2020: RESTORATIVE JUSTICESEBAGAI UPAYA ALTERNATIF PENYELESAIAN TINDAK PIDANADI INDONESIA BERDASARKAN PERATURAN KEJAKSAAN REPUBLIK INDONESIANOMOR 15 TAHUN 2020 - admin, Admin; Putri Qomariyah Dewi Kumala; Samsul Huda; Hasan Basri (STIH Zainul Hasan Kraksaan Kraksaan, 2024)
Abstract Restorative justice is the resolution of criminal cases involving the perpetrator, victim, family of the perpetrator/victim, and other related parties to jointly seek a fair resolution by emphasizing restoration back to its original state, and not retaliation. One of the goals of Restorative Justice is to resolve things together by seeking a fair resolution as a result of the law violation for the benefit of the future. The aim of this research is to find out what mechanisms and efforts are made to achieve restorative justice and what the advantages and disadvantages of restorative justice are. The research approach used in preparing this thesis is normative juridical using a statutory approach. Apart from that, the researcher also uses a conceptual approach so that in this writing the author refers to legal principles. The results of this thesis research show that: (a) Restorative Justice is also one of the principles of law enforcement in resolving cases which can be used as an instrument of recovery. Several mechanisms for resolving prosecutions based on restorative justice according to the Republic of Indonesia Attorney's Regulation Number 15 of 2020 are contained in articles 3, 4, 5 and 6 of the Republic of Indonesia Attorney's Regulation Number 15 of 2020, where the completion of prosecution must meet the requirements for terminating prosecution based on the Republic of Indonesia Attorney's Regulation No. .15 of 2020. (b) Restorative Justice in carrying out its duties also has advantages and disadvantages, one of the advantages of restorative justice is that it not only benefits victims and perpetrators but also society, restorative justice also prioritizes recovery of losses experienced by victims both materially and immaterial. On the other hand, there are shortcomings in restorative justice, namely that restorative justice is not suitable for all criminal acts, only minor crimes. Keywords:Restorative Justice, Criminal Offenses, Termination of Prosecution